Digitalize the purchase process with ERP (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This research aims to address problems related to manual purchasing systems and to design and implement an Odoo-based ERP system in the purchase module at ExhibitOne MICE Solutions. This research employs a qualitative method. The research process begins with preliminary research, problem identification, business process mapping, system requirement analysis, and system implementation. The research findings indicate that the implementation of Odoo ERP is capable of addressing the challenges associated with real-time monitoring of the purchasing system at ExhibitOne MICE Solutions. This research concludes that the implementation of Odoo ERP at ExhibitOne MICE Solutions can effectively integrate the existing modules within the Odoo ERP. The purchase and inventory modules are automatically connected, and every recorded purchase of goods will automatically increase the stock of goods in the inventory section. This can help obtain real-time and accurate information on purchases and the stock of goods.
Keywords: Digitalization; ERP; Oddo; Purchace